The Tropical Virus Unit at Rothamsted - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
The identification, characterization and handling of viruses and other pathogens that can present problems in plant disease diagnosis, such as mycoplasma-like organisms and fastidious bacteria, requires more trained personnel and specialised...